Die altgermanischen Toponyme sowie die ungermanischen Toponyme Germaniens Ein Handbuch zu ihrer Etymologie - Scheungraber, Corinna (Fassbaender, 2014)
This handbook of Old Germanic toponyms is a comprehen-sive collection of Germanic, possibly Germanic and non-Germanic geographical names of Magna Germania and the adjacent provinces. The selection of headwords is based on Hermann Reichert´s Lexikon der altgermanischen Namen (LaN). In the articles, the current state of research concer-ning the localization of the ancient places (, rivers, forests and mountains) and concerning the etymology and word for¬mation of the toponyms is documented and critically dis-cussed.